Food-Choice Values of Elementary School Children and Strategies Used to Influence Mothers' Food Purchasing Decisions. (29th May 2020) - Monalisa, Nazratun; Frongillo, Edward; Blake, Christine; Steck, Susan; DiPietro, Robin
Abstract: Objectives: This study aimed to understand the values held by elementary school children in constructing food choices and the strategies they used to influence their mothers' food purchasing decisions. Methods: Semi-structured qualitative interviews were conducted with 40 elementary school children (aged 6–11 years) and their mothers living in South Carolina. Food choice information was collected only from children and strategies to influence mothers' food purchases were collected from both children and mothers. The interviews were audio-recorded, transcribed verbatim, and open-coded. Coding matrices were used to compare children's and mothers' responses on the children's strategies to influence mothers' food purchasing decisions. Results: Children most valued taste, texture, and flavor of the food items, followed by perceived benefits, happiness, craving, following family and friends, the items' healthfulness, preparation, and presentation when they made food choice decisions. Children reported 157 strategies that they used to influence mothers' purchasing decisions. Mothers had concordance with 80 strategies that children mentioned. In mother-child dyads, more concordance was observed between mothers and sons than between mothers and daughters. The most common and successful strategies from both the children's and mothers' perspectives were reasoned requests, repeated polite requests, and referencing friends. Other strategies included offers to contribute money or service, teaming up with siblings, writing a shopping list, and grabbing desired items. Mothers perceived that children had a lot of influence on their food purchasing decisions. Conclusions: Children were aware of the strategies that would get positive reactions from their mothers. Mothers' acknowledgement of children's influence on their food purchase decisions suggests that children can serve as change agents for improving mothers' food purchases if children prefer healthy foods. Interventions are needed for mothers to help address children's strategies to influence mothers to purchase unhealthy foods and make healthy foods more appealing to children instead of yielding to children's requests for unhealthy items. Funding Sources: SPARC grant and Ogoussan Doctoral Research Award from the University of South Carolina.